Oral Health in South Australia - 2008 - Beckwith, Katie (ARCPOH Population Oral Health Series, 2010)
Oral health in South Australia 2008 provides a comprehensive summary of the oral health of South Australian residents. This publication was developed from a range of surveys conducted by the Australian Research Centre for Population Oral Health (ARCPOH) and administrative data provided by state dental services. Information provided in this publication includes data on caries experience and periodontal diseases of children and adults, tooth retention and loss among adults, access to dental care, cost of dental care and the dental labour force. Information on the oral health of Indigenous children and adults is also provided. The publication highlights the recent increase in the level of dental decay among primary and secondary school children, the low percentage of school aged children visiting the school dental service, the extent of individual out-of-pocket expenditure on dental services, and issues with access to dentists and dental hygienists outside of the Adelaide metropolitan area.